The geometry of hand-sewing : a romance in stitches and embroidery from Alabama Chanin and the School of Making - Chanin, Natalie (Abrams, 2017)
As makers, we tend to learn different stitches over time without thinking much about how they relate to one another. But when Natalie Chanin and her Alabama Chanin and The School of Making teams began to look at needlework closely, they realized all stitches are based on geometric grid systemsand by using grids as guides, they could make learning stitches, even seemingly elaborate ones, as easy as childs play. In The Geometry of Hand-Sewing Chanin presents their breakthrough method, featuring illustrated instructions (for both right- and left-handed stitchers) for more than 100 stitchesfrom the most basic straight and chain to the more fanciful feather and herringbone; photos of both right and wrong sides; and guidelines for modifying stitches to increase ones repertoire further. To simplify learning, the book also includes two plastic stitching cards die-cut with the grids on which every stitch in the book is based. These reusable cards can be stitched through for practicing ( just as children use lacing cards to learn to tie shoes) or used as stencils for transferring grids to fabric.